2021
DOI: 10.3390/children8090758
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oral Sensory-Motor Stimulation in Premature Infants in the Neonatal Intensive Care Unit (NICU) Systematic Review

Abstract: The aim of this study was to identify and to assess the best evidence currently available on the effectiveness of oral sensory-motor stimulation in preterm infants in the neonatal intensive care unit. We performed a systematic review following the Preferred Reporting Items for Systematic Reviews (PRISMA) statements. The search was conducted using the Pubmed, Web of Science (WOS), PEDro and Scopus databases. Clinical trials were reviewed and PEDro rating scale was used to assess the methodological quality of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In the systemic review of Rodriguez Gonzalez P ( 12 ), oral sensorimotor stimulation did not reveal superior results on the infants' physiological data and breastfeeding skills. However, in our study, infants in the study group significantly differed in transferring to the mother's breast after discharge, even if they were not discharged.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In the systemic review of Rodriguez Gonzalez P ( 12 ), oral sensorimotor stimulation did not reveal superior results on the infants' physiological data and breastfeeding skills. However, in our study, infants in the study group significantly differed in transferring to the mother's breast after discharge, even if they were not discharged.…”
Section: Discussionmentioning
confidence: 88%
“…Based on a systematic review of relevant studies ( 12 ), it was found that the implementation of oral-motor therapy for preterm infants in the NICU yields favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…145,146 Speech-language pathologists can provide strategies to support safe oral feeding and to mitigate oral aversion, including oral sensory motor stimulation, which has been shown to support independent oral feeding in premature infants. 147 Practice recommendations for critically ill children include early mobility and rehabilitative strategies to support passive range of motion, positioning, readiness for mobility, assisted transfers, and ambulation. 148 Supporting Transition From Hospital to Home…”
Section: Habilitative Servicesmentioning
confidence: 99%
“…Preterm newborns frequently experience delays in the development of their oral feeding and motor abilities because they don't get the same in-utero oral motor practice that comes from swallowing amniotic fluid [ 28 ]. Because of their underdeveloped reflexes, reduced muscle tone around the mouth, and diminished sensitivity and strength in their tongue, preterm newborns frequently have impaired oral motor control [ 19 , 29 ].…”
Section: Reviewmentioning
confidence: 99%